Studies on potential of sulphonic acid-doped polyaniline as oxygen sensor / Sarifah Fauziah Syed Draman, Rusli Daik and Musa Ahmad - Syed Draman, Sarifah Fauziah; Daik, Rusli; Ahmad, Musa (2008)
Potential of three conjugated polymers namely suIphonic acid-doped polyanilines (sulphuric acid doped polyaniline (SPAN), dodecylbenzene sulphonic acid-doped polyaniline (DBSA-doped PANI) and champor sulphonic acid -doped polyaniline (CSA-doped PANI)) as sensing agents for O2 gas detection in terms of fluorescence quenching was studied. Sensing tests were carried out on polymer samples in the form of solution by using fluorescence spectrometer. SPAN solution was excited at 308 nm and the maximum emission was observed at 363 nm. DBSA-doped PANI solution and CSA-doped PANT solution were excited at 313 nm. Meanwhile, the maximum emission for DBSA-doped PANI solution and CSA-doped PANI solution were observed at 373 nm and 395 nm, respectively. Samples of polymer solution showed positive response towards O2. Results showed that the intensity of the fluorescence decreased when exposed to O2 gas. All polymer solutions were fully regenerated by using N2 gas within 1 hour period. Photostability study showed that all samples of polymer solution were stable towards light when continuously exposed to xenon lamp for 9 hours. The relative standard deviation (RSD) values for SPAN solution, DBSA doped PANI solution and CSA-doped PANI solution for repeatability were 0.23 %, 0.64 % and 0.76 %, respectively. Meanwhile RSD values for reproducibility were 2.36 %, 6.98 % and 1.27 %, respectively. The study on effect of the flow rate on the response time was carried using 3 different rates which were 0.25 mL/s, 1.00 mL/s and 2.00 mL/s. Results obtained showed that the higher the flow rate, the shorter the response time.